Protection of Patent Rights in the Genetic Engineering Development to Support the Development of New Capital City of Indonesia (Faculty of Law, Universitas Negeri Semarang, 2022)
This set of laws investigates the best ways to build a science on the foundation of genetic engineering and to offer patent protection for products that have been genetically engineered in the new capital city of Indonesia. Genetic engineering requires knowledge of medicine, including drugs and healing procedures, as well as knowledge related to genetic resources, a separate institution is required to study, research, and develop the inherent potentials in the new capital city. This is because genetic engineering includes technical skills, craftsmanship, agricultural knowledge, ecological knowledge, and knowledge of genetic resources. In order for subsequent inventors to be able to compete and develop new genetic engineering technologies, legal protection is absolutely necessary in today's global competition. The purpose of the government's efforts to provide legal protection for patent rights on genetic products is to provide full support to the general public. This will be accomplished by facilitating public access to legal protection by registering intellectual property rights in the field of patents. In a similar vein, the progression of genetic engineering will be protected by the registration of its patent, and its effects will be able to be felt by the people living in the new capital city as well as the areas that surround it. Keywords: Patent Rights, Genetic Engineering, New Capital City